Beyond the Mummy Track? Part-time Rights, Gender, and Career-Family Dilemmas - Grönlund, Anne; Öun, Ida (Nordic Journal of Working Life Studies, 2018)
Statutory rights to part-time work are increasingly discussed and institutionalized, but have been little empirically investigated. On the basis of a survey of Swedish parents (n = 1900), the article explores the usage and usefulness of the right to work hour reductions in relation to career-family dilemmas. The results show that the gender composition of the workplace affects both mothers’ and fathers’ likelihood of reducing work hours. Mothers who reduce work hours experience lower work-family conflict but stronger fears of negative career repercussions. For fathers, the implications of work hour reductions vary with the gender composition of the workplace. Meanwhile, the division of housework is related both to the likelihood of reducing work hours and to its implications. The analysis suggests that even when a statutory right to part-time is provided, workplace norms and men’s participation in housework are crucial for changing gender patterns.